A new edition of the Norman Pipe Rolls - Vincent Moss (Tabularia)
The article introduces the first volume of the new edition of the Norman Pipe Rolls and critically examines previous editions. It argues that the Stapleton edition was never finished (due to his ill health) and that manuscripts he failed to thoroughly examine provide the key to understanding the Norman pipes i.e. that these rolls were not made at the seating of the Norman Exchequer but are copies. It argues that all previous comparisons between the forms of the English and Norman pipe roll are therefore redundant since the Norman manuscripts can only be compared to the unpublished chancery and other copies of the English Exchequer which the Norman Pipe rolls strongly resemble.